2018
DOI: 10.1021/acs.biochem.8b00728
|View full text |Cite
|
Sign up to set email alerts
|

A Noncanonical Metal Center Drives the Activity of the Sediminispirochaeta smaragdinae Metallo-β-lactamase SPS-1

Abstract: In an effort to evaluate whether a recently reported putative metallo-β-lactamase (MβL) contains a novel MβL active site, SPS-1 from Sediminispirochaeta smaragdinae was overexpressed, purified, and characterized using spectroscopic and crystallographic studies. Metal analyses demonstrate that recombinant SPS-1 binds nearly 2 equiv of Zn(II), and steady-state kinetic studies show that the enzyme hydrolyzes carbapenems and certain cephalosporins but not β-lactam substrates with bulky substituents at the 6/7 posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Uptake transporters such as OATP2B1, PEPT1 and sodium-dependent bile acid transporter (ASBT/SLC10A2) are involved in the intestinal uptake of drugs across the brush border membrane 75 . For example, PEPT1 transports di/tripeptides-like anticancer drugs such as bestatin and β -lactam antibiotics into enterocytes76, 77, 78. Efflux transporters expressed on the brush border membrane of the intestine, are considered as the barriers for intestinal drug absorption.…”
Section: Determinants Of Pkmentioning
confidence: 99%
“…Uptake transporters such as OATP2B1, PEPT1 and sodium-dependent bile acid transporter (ASBT/SLC10A2) are involved in the intestinal uptake of drugs across the brush border membrane 75 . For example, PEPT1 transports di/tripeptides-like anticancer drugs such as bestatin and β -lactam antibiotics into enterocytes76, 77, 78. Efflux transporters expressed on the brush border membrane of the intestine, are considered as the barriers for intestinal drug absorption.…”
Section: Determinants Of Pkmentioning
confidence: 99%
“…Despite some significant sequence heterogeneity with SPM-1, the protein alignment between the two enzymes revealed conserved amino acid residues known to be crucial for the hydrolytic activity of MβLs, such as the histidine residues 116, 118, 196, and 263, the aspartic acid residue 120, and the cysteine residue 221, respectively (Figure 1; Meini et al, 2014). Phylogenetic analysis using the alignment software SeaView showed that PAN-1 is the closest relative enzyme to SPM-1 (Figure 2) and to the recently reported SPS-1 B1 MβL (Cheng et al, 2018). Interestingly, PAN-1 and SPS-1 exhibited a central inserted sequence that was considered as a unique feature of the SPM-1 MβL (Figure 1; Murphy et al, 2006; Meini et al, 2014; González et al, 2018).…”
Section: Resultsmentioning
confidence: 52%
“…Our study characterized a novel MβL from an environmental isolate recovered from a coral. This enzyme showed the highest amino acid identity with the class B carbapenemase SPM-1 being its closest relative after the recently reported SPS-1 enzyme (Figure 2; Cheng et al, 2018)(. Interestingly, the amino acid sequence of PAN-1 exhibits an inserted sequence that was also described in SPM-1 (Murphy et al, 2003), being an original feature comparing to other subclass B1 MβLs (Figure 1).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The proteins encoded by these genes are primarily associated with biochemical or signaling pathways at the cellular level and defects in expression may lead to certain disorders. For instance, anomalies in PHETA1/2 have been associated with abnormal bone formation resulting in craniofacial defects ( Ates et al, 2020 ), HAGH has been associated with skin, bone and joint infections in Yaws disease ( Cheng et al, 2018 ) and mutations in GFPT1 have been associated with muscle weakness in congenital myasthenic syndrome ( Helman et al, 2019 ). In addition, histone-related genes H2B Clustered Histone 21 ( H2bc21 ) and H2bc4 were also significantly upregulated during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%